Ebola Virus Disease: international perspective on enhanced health surveillance, disposition of the dead, and their effect on isolation and quarantine practices. Issue 1 (December 2016) - Emrick, Preeti; Gentry, Christine; Morowit, Lauren
Abstract Despite the comparatively few cases of Ebola Virus Disease (EVD) that arose outside of Sierra Leone, Guinea, and Liberia in 2014, public health response partners around the world developed a patchwork of plans and policies to monitor thousands of people exposed to EVD, quarantine suspected cases, isolate confirmed cases, and close borders to prevent further spread of the disease. Deeply affected countries such as Sierra Leone, Guinea, and Liberia, as well as less affected countries such as the United States, Canada, and Australia developed special guidance regarding isolation and quarantine measures for EVD. The massive and well-publicized EVD response highlighted international challenges of public health laws and policies, many of which remain largely unchanged since their implementation. This article examines public health measures, including health surveillance and decedent disposition, and their effects on isolation and quarantine practices in six countries (Sierra Leone, Guinea, Liberia, United States, Canada, and Australia) in context of the 2014–2015 EVD response, and makes recommendations.